Impact on the effectiveness of rehabilitation funds qualified athletes specializing in the long jump with a running start - T.B. Kutek (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Purpose . Experimentally verify the effectiveness of recovery funds allocated to skilled performance athletes who specialize in the long jump with a running start. Material . In the experiment involved 12 athletes. The data obtained were tested under conditions of multiple repetition of jumping from the middle run (11-12 crossovers). All athletes performed a series of six jumps 3 min rest interval. Results . Under normal conditions of athletic training was analyzed effects specially designed training complex effects ( exercise and massage techniques ) aimed at stimulating specially trained skilled athletes who specialize in the long jump with a running start. Designed training complex influences can be effectively used in conditions of competitive activity, and in the process of training. Conclusions . The results showed the possibility of using special exercises aimed at stimulation of special readiness and effectiveness of athletes who specialize in the long jump with a running start.